Pengaruh Stres Kerja, Motivasi Kerja, Kompensasi, dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT CRI: The Effect of Job Stress, Work Motivation, Compensation, Job Satisfaction on Employee Performance at PT CRI - Muhammad Rayno Septian; Popong Nurhayati; Arry Ekananta (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Companies serve as institutions where economic actors interact to achieve specific goals. The success of a company is heavily influenced by the quality and capability of its human resources. To attain optimal performance, human resources play a crucial role in realizing company objectives. This study investigates the impact of work pressure, work motivation, and compensation on employee performance at PT Citra Resins Industries.Purpose: The research focuses on determining how these factors affect employee performance and satisfaction within a specific organizational context.Design/methodology/approach: This study examines 77 employees at PT Citra Resins Industries using a quantitative approach to identify relationships between the variables.Findings/Result: The findings of this study demonstrate that work stress exerts a significant influence on employee performance at PT Citra Resins Industries, highlighting the critical role of effective stress management in enhancing organizational productivity. Furthermore, work motivation is shown to positively contribute to employee performance, emphasizing the importance of fostering a motivational work environment to achieve optimal outcomes. However, compensation does not exhibit a direct effect on employee performance, indicating that financial incentives alone may not suffice to drive employee productivity. As an intervening variable, job satisfaction is affected by work stress but remains unaffected by work motivation or compensation. These findings suggest that to enhance job satisfaction, the organization should prioritize reducing work stress. Meanwhile, additional strategies may be required to maximize the impact of work motivation and compensation on employee satisfaction and performance.Conclusion: Work stress and motivation are critical drivers of employee performance. Companies must strategically address these factors while reevaluating their compensation structures to enhance satisfaction and performance outcomes.Originality/value (State of the art): This research highlights the unique organizational dynamics at PT Citra Resins Industries, providing valuable insights for companies facing similar challenges in managing employee stress, motivation, and compensation. Keywords: employee performance, employee satisfaction, work motivation, sem-pls, work stress